Unveiling and Taming Liabilities of Aspect Libraries Reuse - Coelho, Roberta; Kulesza, Uirá; Rashid, Awais; von Staa, Arndt; Lucena, Carlos (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2008: Anais do XXII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2008.21325, 2008)
Aspect Libraries have introduced new possibilities of application composition, facilitating the reuse of crosscutting functionalities. However, if on the one hand this facilitates the independent development of reusable aspects, on the other hand it can bring additional complexity to software reuse, especially, in exception-aware systems. In this work, we present a set of potential fault scenarios associated with aspect libraries reuse. We show that the reuse of aspect libraries is indeed fault prone in exceptional conditions and present a principled reuse approach supported by a static analysis tool that leads to significant improvements.